Generation of mouse spermatogonial stem-cell-colonies in a non-adherent culture - Azizi, Hossein; Skutella, Thomas; Shahverdi, Abdolhossein (Cell journal (Yakhteh), 2017)
Objective: The properties of self-renewal and division in spermatogonial stem cells (SSCs) support spermatogenesis. There is a number of reported methods for in vitro SSC culture systems. The development of a culture system that effectively supports isolation and selfrenewal of germline stem cells (GSCs) is of tremendous benefit for clinical trials, experimental research, and as potential treatment for male infertility. The current study aims to consider the cultivation and behavior of GSCs in a non-adherent culture system. Materials and Methods: In this experimental study, we cultured testicular cells from neonatal mice in agarose coated plates in the presence of Dulbecco’s modified Eagle’s medium (DMEM) medium (CTRL group), 10% fetal bovine serum (FBS)+DMEM (10% group), and growth factor (G group) that contained 2% FBS, glial cell-derived neurotrophic factor (GDNF), epidermal growth factor (EGF), and fibroblast growth factor (FGF). Mouse spermatogonial stem-like colonies were isolated approximately 3 weeks after digestion of the testis tissue. After passages 2-3, the identity of the mouse spermatogonial stem-like cells was confirmed by immunocytochemistry, reverse transcription-polymerase chain reaction (RT-PCR), and flow cytometry against the germ cell markers α6, β1, c-Kit, Thy-1, c-Ret, Plzf, and Oct4. The statistical significance between mean values in different groups was determined by one-way analysis of variance (ANOVA). Results: We observed spermatogonial stem-like colonies in the G and 10% groups, but not the CTRL group. Immunocytochemistry, flow cytometry, and RT-PCR confirmed expressions of germ cell markers in these cells. In the spermatogonial stem-like cells, we observed a significant expression (P<0.05) of germ cell markers in the G and 10% groups versus the testis cells (T). Their proliferative and apoptotic activities were examined by Ki67 and PI/annexin V-FITC. Alkaline phosphatase assay showed that mouse spermato-gonial stem-like colonies were partially positive. Conclusion: A non-adherent culture system could provide a favorable method for in vitro short-term culture of spermatogonial stem-like cell colonies.